Path formulation for Z(2) circle plus Z(2)-equivariant bifurcation problems - Ferreira Costa, Joao Carlos; Sitta, Angela Maria (Birkhauser Boston, 2007)
M. Manoel and I. Stewart 0101) classify Z(2) circle plus Z(2)-equivariant bifurcation problems up to codimension 3 and 1 modal parameter, using the classical techniques of singularity theory of Golubistky and Schaeffer [8]. In this paper we classify these same problems using an alternative form: the path formulation (Theorem 6.1). One of the advantages of this method is that the calculates to obtain the normal forms are easier. Furthermore, in our classification we observe the presence of only one modal parameter in the generic core. It differs from the classical classification where the core has 2 modal parameters. We finish this work comparing our classification to the one obtained in [10].
Keywords: path formulation; equivariant bifurcation problems; Z(2) circle plus Z(2)-symmetry; classification